Solid phase extraction and preconcentration of cobalt in mineral waters with PAR-loaded Amberlite XAD-7 and flame atomic absorption spectrometry - Ince, Muharrem; Kaya, Gokce; Yaman, Mehmet (Springer Heidelberg, 2010)
A simple, sensitive, accurate, and selective method for determination of ultratrace levels of Co is modified. The method is based on preconcentration of Co on the PAR-loaded Amberlite XAD-7 at pH 2.0 +/- A 0.2 for contact time as low as 45 min. The adsorbed cobalt was eluted with concentrated nitric acid and measured by flame atomic absorption spectrometry. Recoveries up to 90% were achieved. The optimized preconcentration method was applied to cobalt determination in natural mineral waters. The detection limit was found to be 0.1 ng mL(-1). The relative standard deviation was found to be 13% for 600 mL of 2.0 ng mL(-1), for 10 replicate preconcentration procedures. Cobalt concentrations in the studied water samples were found to be in the ranges of 0.5-3.5 ng mL(-1).
Keywords: Cobalt; Natural mineral water; XAD-7; PAR; Atomic absorption; Preconcentration